2016
DOI: 10.1016/j.reu.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Nivel de autonomía de enfermeras en la práctica pediátrica. Una experiencia chilena

Abstract: Autonomía profesional;Enfermeras clínicas; Enfermería pediátrica; Enfermería práctica; Chile Resumen Objetivo: Determinar el nivel de autonomía que perciben las enfermeras pediátricas en su ejercicio profesional. Métodos: Estudio transversal observacional analítico en una población de 31 enfermeras pediátricas de un hospital público de Valdivia, Chile. Se aplicó un cuestionario previamente traducido, adaptado transculturalmente y validado por juicio experto. Se determinó el nivel de autonomía en acciones asist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
5
0
4
Order By: Relevance
“…In the midst of the uncertainties with regard to the virus, there is no doubt that, at the end of the pandemic, nursing and the provision of health care will be stronger and better prepared to face future challenges (9) . However, only time can tell whether the practices implemented by nurses to manage the new coronavirus pandemic will remain, after this period of public calamity is over.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the midst of the uncertainties with regard to the virus, there is no doubt that, at the end of the pandemic, nursing and the provision of health care will be stronger and better prepared to face future challenges (9) . However, only time can tell whether the practices implemented by nurses to manage the new coronavirus pandemic will remain, after this period of public calamity is over.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the professional autonomy of nurses is seen as a complex question, due to influences from the social structure in which the work is carried out and to the obstacles daily life imposes for this to be achieved. Resisting these influences and overthrowing the barriers that prevent consolidating professional autonomy enables a better performance and strengthen the relationship between health team members and patients and their relatives (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that work occupies a prominent place in the life of the people, it is essential to make it possible to express the subjectivity of workers and to boost their participation in the planning and organization of work (12) . Research with the objective of determining the level of autonomy that pediatric nurses perceive in their work found that the assistance tasks are developed with greater independence, especially the actions of education and health promotion, while in the development of the administrative functions are shown more dependents (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Se puede observar en sus postulados que el concepto de la "enfermera como auxiliar del médico" queda sin sustento, porque la enfermera es independiente en cada una de sus acciones cuando la situación lo amerite (10)(11)(12)(13)(14), generando un mayor interés por las enfermeras a nivel mundial por el posicionamiento de la enfermería como profesión autónoma (16,17).…”
Section: Introductionunclassified
“…Al ser una ciencia joven, la enfermería ha tenido grandes progresos en su desarrollo disciplinar, centrados en la búsqueda continua de la autonomía y la independencia de la profesión, tanto en el ejercicio profesional como en el desarrollo científico, sin embargo a pesar de todos los esfuerzos realizados, la enfermería ha tenido una serie de dificultades por la dependencia, subordinación y por poderes hegemónicos en el sistema de salud desde sus inicios, lo cual ha sido un factor determinante para lograr de manera definitiva una emancipación profesional, un quehacer autónomo e indelegable y delimitar de manera específica su campo de conocimiento y desempeño profesional (12,17) .…”
Section: Introductionunclassified